INTERPERSONAL RELATIONS IN THE FAMILY – A KEY TO PEACE IN SOCIETY (Scientific journal of the Fergana State University, 2023)
As human society develops, the urgency of family issues will increase accordingly, and the focus on the family will be higher tomorrow than yesterday and today. Because the family is a small part of society, and the more harmonious, harmonious and strong it is, the stronger the society will be. In this article, we will talk about improving interpersonal relationships in the family and shaping family culture.